2023
DOI: 10.31616/asj.2022.0065
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Reuptake Inhibitor Increases Pseudarthrosis Rates in Anterior Cervical Discectomy and Fusions

Abstract: To determine (1) the effects of serotonin reuptake inhibitors in pseudarthrosis rates after anterior cervical decompression and fusion (ACDF) and ( 2) to identify patient-reported outcome measures in patients taking serotonin reuptake inhibitors. Overview of Literature: Recent literature suggests that selective serotonin reuptake inhibitors (SSRIs) may inhibit fracture healing via downregulation of osteoblast differentiation. Spinal fusion supplementation with osteoblast-rich substances enhances spinal fusion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Various factors affect cage subsidence, including overdistraction, endplate preparation, and appropriate cage size. However, information concerning the factors affecting subsidence following ACDF is limited [ 3 , 5 7 , 14 , 16 , 17 ]. Lee et al [ 3 ] analyzed the risk factors for subsidence following ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors affect cage subsidence, including overdistraction, endplate preparation, and appropriate cage size. However, information concerning the factors affecting subsidence following ACDF is limited [ 3 , 5 7 , 14 , 16 , 17 ]. Lee et al [ 3 ] analyzed the risk factors for subsidence following ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective cohort studies, Adogwa et al36,37 found that preoperative depression, measured by the Zung Depression Scale, was associated with increased rates of symptomatic pseudarthrosis after lumbar spinal fusion surgery. In contrast, Lambrechts et al38 demonstrated that a diagnosis of depression was not independently predictive of radiographic pseudarthrosis in ACDF. Although the literature on other mental health disorders is sparse, further research is needed to determine whether optimization of a person's mental health before spinal fusion surgery can reduce their risk of developing pseudarthrosis.…”
Section: The Impact Of Poor Mental Health On Outcomesmentioning
confidence: 91%
“…More specifically, these medications seem to stimulate osteoclasts while inhibiting bone mineralization and differentiation of osteoblasts 41,42. Several clinical studies have demonstrated the negative effects of antidepressants on bone healing and fracture risk 34,38,43,44. In particular, Lambrechts et al38 demonstrated that antidepressants (SSRIs, selective serotonin-norepinephrine reuptake inhibitors, and tricyclic antidepressants) were independently associated with radiographic pseudarthrosis after ACDF.…”
Section: The Impact Of Poor Mental Health On Outcomesmentioning
confidence: 99%
See 1 more Smart Citation